MAKNA IDEASIONAL PADA TEKS KASUS SOEHARTO OLEH PIHAK PRO DAN KONTRA (KAJIAN MELALUI SISTEM TRANSITIVITAS) - Marlia, Marlia (Universitas Muhammadiyah Surakarta, 2008)
This article presents the linguistic phenomena in the text of Suhartoâs cases both by the pros and cons sides. The texts are taken from internet accessed on May 30.2008. The analysis used is referring to Faircloughâs critical discourse analysis: phe- nomenology-interpretative and the combination of both qualitative and quantita- tive approaches. However, the analysis applies Hallidayâs Systemic Functional Gram- mar, especially in the system of its transitivity. The result shows that there is a contradictory in the act sequence between the pros and cons sides. The pros texts are more humane than the cons ones. Moreover, the pros genres are narrative and recount, and they tend to be emosional, while the cons one is report and tends to be rational. The ideology within the pros text is humanism and feudalism, while within the cons one is democratism/equality.Â Key words: makna ideasional, teks, sistem transitivitas, CDA, dan genre.